The relationship among perceived teammates support, positive emotions, self-esteem and well-being - Tan, Hui Yi (2019)
Dual role of a student and athlete can result in stress and affect the student-athletes’ well-being. Past literature has identified social support as one of the variables that can improve well-being. However, there is a lack of studies that focus on teammates support. Based on SOR model and broaden-and-build theory, this study examined if the perception of teammates support can influence well-being through positive emotions and self-esteem. Findings of this study are beneficial for coaches or student-leaders to design strategies to improve well-being of student-athletes. A total of 336 participants who are student-athletes in Singapore Universities took part in this study through completing either an online or hardcopy survey and 313 data were valid for analysis. Analysis of data was done through Statistical Package for Social Science (SPSS) to remove univariate and multivariate outliers as well as through the use of Analysis of Moment Structures (AMOS) for the testing of Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM). Results indicated that perceived teammates support has positive influence on well-being through positive emotion and/or self-esteem. However, there is no direct influence from perceived teammates support to well-being. The findings support the important role of perceived teammates support in enhancing well-being through positive emotions and self-esteem.